Perancangan dan Pembuatan Media Pembelajaran Dasar-Dasar Program Keahlian Berbasis Android di Sekolah Menengah Kejuruan (SMK) - Deya Husnul Khatimah; Rini Sefriani; Indra Wijaya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research and development is motivated by the problem of limited learning media in the Fundamentals of the Skills Program at SMK Kartika 1-2 Padang in the odd semester of the 2022/2023 academic year. Causing students difficulty in understanding the material. Therefore, the authors designed an attractive learning media. This study aims to determine the validity, practicality and effectiveness of making learning media applications for Fundamentals of Android-Based Skills Programs in Vocational High Schools (SMK). This research uses the R&D research development method (research & development). The research model used is the ADDIE development model, with the following development steps: (1) Analyze, (2) design, (3) development, (4) implementation and (5) evaluate. The research subjects were 34 people. The results of the validity test by the validator of Android-based learning media as a whole obtained an average of 91.69% with a very valid interpretation. The practicality test was obtained at 92.93% with a very practical interpretation. The effectiveness test was obtained at 98.12% with a very effective interpretation. It was concluded that the research instrument was very valid, very practical and very effective to use at SMK Kartika 1-2 Padang in class X TKJ.